Low-grade Myxofibrosarcoma in the Mandible: A Rare Case Report - Neda Kargahi; Elham Arjang; Shirin Shahnaseri; Forooz Keshani (Middle East Journal of Cancer, 2017)
Myxofibrosarcoma is a malignant neoplasm of connective tissue origin commonly found in the extremities. It is very rare in the head and neck regions. Only 25 cases of myxofibrosarcoma have been reported in the head and neck regions until 2014. Here we report a 61-year-old male with this neoplasm in the lower border of his mandible. During a two-year follow-up, this case recurred four times despite a complete resection. This study suggested combined surgical and adjuvant radiotherapy for unresectable lesions and tumors with positive margins to prevent recurrence and risk of progression.